PAI Teacher Leadership Paradigm in Achieving Learning Optimization at SMPIT Titian Ilmu Bekasi - Sandy Sandy; Nurhamzah Nurhamzah; Siti Ismilah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Nowadays, students are required to be able to apply Islamic Religious Education (PAI) lessons in their daily lives, so pai teacher leadership is needed to achieve this goal. The purpose of this study is to find out the paradigm of PAI teacher leadership, to find out the problems of PAI teachers, and to find out the leadership of PAI teachers in achieving learning optimization at SMPIT Titian Ilmu Bekasi. This research uses a qualitative approach with the content analysis method (content study). Data collection techniques with literature review and observation. The results of this study are (1) the leadership of a PAI teacher can be measured by benchmarking the extent to which he can implement leadership indicators. (2) Some of the problems of PAI teachers include insufficient student interest, less conducive subject hours, lack of mastery of the material, and uninteresting learning methods or media. (3) The leadership of pai teachers at SMPIT Titian Ilmu Bekasi is in accordance with effective leaders, in accordance with the leadership component and in accordance with leadership in the Islamic view, although not perfectly but already represents the overall nature of teacher leadership in the Islamic view